The association of urinary cadmium with sex steroid hormone concentrations in a general population sample of US adult men - Basaria Shehzad; Rohrmann Sabine; Shiels Meredith S; Guallar Eliseo; Menke Andy; Rifai Nader; Nelson William G; Platz Elizabeth A (BMC, 2008)
Abstract Background Studies investigating the association of cadmium and sex steroid hormones in men have been inconsistent, but previous studies were relatively small. Methods In a nationally representative sample of 1,262 men participating in the morning examination session of phase I (1998-1991) of the third National Health and Nutrition Examination Survey, creatinine corrected urinary cadmium and serum concentrations of sex steroid hormones were measured following a standardized protocol. Results After adjustment for age and race-ethnicity, higher cadmium levels were associated with higher levels of total testosterone, total estradiol, sex hormone-binding globulin, estimated free testosterone, and estimated free estradiol (each p-trend < 0.05). After additionally adjusting for smoking status and serum cotinine, none of the hormones maintained an association with urinary cadmium (each p-trend > 0.05). Conclusion Urinary cadmium levels were not associated with sex steroid hormone concentrations in a large nationally representative sample of US men.